Are Disagreements in Caregiver and Patient Assessment of Patient Health Associated with Increased Caregiver Burden in Caregivers of Older Adults with Cancer?. (14th August 2017) - Hsu, Tina; Loscalzo, Matthew; Ramani, Rupal; Forman, Stephen; Popplewell, Leslie; Clark, Karen; Katheria, Vani; Strowbridge, Rex; Rinehart, Redmond; Smith, Dan; Matthews, Keith; Dillehunt, Jeff; et al.
Abstract: Background: As patients age, caregivers increasingly provide essential support and patient information. We sought to determine if patient‐caregiver assessments of patient health differ and if differences contribute to burden in caregivers of older adults with cancer. Materials and Methods: One hundred patients, aged ≥65, and their caregivers independently assessed patient function, comorbidity, nutrition, social activity, social support, and mental health. Caregivers completed the Caregiver Strain Index (CSI). Patient‐caregiver assessments were compared using the Wilcoxon signed rank test and paired t test. Association between caregiver burden and differences between patient‐caregiver assessments was examined using generalized linear regression. Results: Median patient age was 70 (range 65–91) and 70% had advanced disease. Sixty percent of patients reported requiring help with instrumental activities of daily living (IADLs); most had good social support (median Medical Outcomes Study [MOS]‐Social Support Survey score 92) and mental health (median Mental Health Inventory score 85). Caregivers were a median age of 66 (range 28–85), 73% female, 68% spousal caregivers, and 79% lived with the patient. Caregivers rated patients as having poorer physical function (more IADLs dependency [ p  = .008], lower Karnofsky Performance Status [ p  = .02], lower MOS‐Physical Function [ p  < .0001]), poorer mental health ( p  = .0002), and having more social support ( p  = .03) than patients themselves. Three‐quarters of caregivers experienced some caregiver burden (mean CSI score 3.1). Only differences in patient‐caregiver assessment of the patient's need for help with IADLs were associated with increased caregiver burden ( p  = .03). Conclusion: Patient‐caregiver assessments of patient function, mental health, and social support differ. However, only differences in assessment of IADLs dependency were associated with increased caregiver burden. Abstract : Cancer‐related therapy is increasingly administered in the outpatient setting, resulting in increased dependence on caregivers suggest to provide physical and emotional support to patients. This article describes differences in patient versus caregiver assessments of patient health, considering caregiver perceptions of the patient's health and abilities compared to that reported by the patient.